Transformation of Islamic Education Based on Artificial Intelligence Technology in Building Moderate Character and Global Competence in Today's Students - Dwi Noviatul Zahra (LP3M Pascasarjana STAI Ibnurusyd, 2026)
This study examines the transformation of Islamic education through the integration of Artificial Intelligence (AI) technology in fostering moderate character and global competence among today’s students. The rapid advancement of digital technology demands an adaptive educational model that not only emphasizes cognitive achievement but also strengthens ethical values and religious moderation. This research employs a qualitative approach through literature review and conceptual analysis of current practices in Islamic education and AI-based learning systems. The findings indicate that AI can support personalized learning, enhance critical thinking, and facilitate access to diverse religious perspectives, which are essential in cultivating inclusive and tolerant attitudes. Furthermore, the integration of AI in Islamic education encourages the development of global competencies, including digital literacy, cross-cultural understanding, and problem-solving skills. However, this transformation also requires careful consideration of ethical principles, teacher readiness, and curriculum design to ensure alignment with Islamic values. The study concludes that AI-based Islamic education has significant potential to create a balanced learning environment that integrates technological advancement with spiritual and moral development, ultimately preparing students to navigate global challenges while maintaining a moderate and inclusive religious outlook.